Auditing information systems - Champlain, Jack J. (Finance professional collection, 2003)
Have you been asked to perform an information systems audit and don't know where to start? Examine a company's hardware, software, and data organization and processing methods to ensure quality control and security with this easy, practical guide to auditing computer systems--the tools necessary to implement an effective IS audit. In nontechnical language and following the format of an IS audit program, you'll gain insight into new types of security certifications (e.g., TruSecure, CAP SysTrust, CPA WebTrust) as well as the importance of physical security controls, adequate insurance, and digi.